Amaranthus Lycopersicum Juice terhadap Kadar Hemoglobin Ibu Hamil dengan Anemia - Rahayu, Fitria Yulianti; Suryati, Yayat; Murtiningsih, Murtiningsih; Hidayat, Monna Maharani; Maryati, Ida (Journal of Telenursing (JOTING), 2025)
This study aims to identify the effect of giving Amaranthus lycopersicum Juice on increasing hemoglobin in pregnant women with anemia. The method used is a quasi-experimental one-group pretest and repeated posttest design. The results showed a significant effect of Amaranthus lycopersicum Juice intervention on increasing hemoglobin levels in pregnant women with anemia, as evidenced by a p-value of 0.000. In addition, the results obtained based on the GLM-RM analysis showed a significant effect of Amaranthus lycopersicum Juice intervention according to time on increasing hemoglobin levels in pregnant women with anemia, as evidenced by a p-value of 0.000. In conclusion, giving Amaranthus lycopersicum Juice has an effect on increasing hemoglobin in pregnant women with anemia. Keywords: Amaranthus lycopersicum, Anemia, Hemoglobin, Pregnant Women